PERAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN AKHLAK PESERTA DIDIK DI ERA DIGITAL - Yanah Yanah; Wahyu Musrifah Ramadani; Sahrul Gunawan; Fina Dwi Novitasari; Devy Habibi Muhammad (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This research focuses on the role of Islamic Religious Education in shaping students' character, particularly in the context of peer relationships at school, which exhibit signs of moral decline. The research problem formulation includes the role of Islamic Religious Education in student friendships and the characteristics that emerge in their social interactions. The results of this research are expected to provide theoretical and practical benefits. Theoretically, this research is expected to enrich understanding of the importance of Islamic Religious Education in the dynamics of friendship for the formation of student character. From a practical perspective, this research can be a means to increase experience in the world of education and the real world, provide guidance to students in choosing positive peers, increase parental awareness to pay more attention to and supervise their children's social environment, and serve as a reference for schools to improve supervision of students.